Advances in determining abdominal aortic aneurysm size and growth - Kontopodis, Nikolaos (World J Radiol, 2016)
Abdominal aortic aneurysm is a common pathology in the aging population of the developed world which carries a significant mortality in excess of 80% in case of rupture. Aneurysmal disease probably represents the only surgical condition in which size is such a critical determinant of the need for intervention and therefore the ability to accurately and reproducibly record aneurysm size and growth over time is of outmost importance. In the same time that imaging techniques may be limited by intra- and inter-observer variability and there may be inconsistencies due to different modalities [ultrasound, computed tomography (CT)], rapid technologic advancement have taken aortic imaging to the next level. Digital imaging, multi-detector scanners, thin slice CT and most- importantly the ability to perform 3-dimensional reconstruction and image post-processing have currently become widely available rendering most of the imaging modalities used in the past out of date. The aim of the current article is to report on various imaging methods and current state of the art techniques used to record aneurysm size and growth. Moreover we aim to emphasize on the future research directions and report on techniques which probably will be widely used and incorporated in clinical practice in the near future.